Evaluating and Restructuring Library Specialization Strategies: A Case Study of Pyeongchang County - Ro, Ji Yoon; Noh, Younghee; Chang, Inho (International Journal of Knowledge Content Development & Technology, 2025)
This study diagnoses the outcomes and limitations of thematic specialization in Pyeongchang County’s public and small libraries and proposes a sustainable re-specialization model. Through literature review, current status analysis, and survey research, the implementation of the 1st Mid- to Long-term Development Plan (2020-2025) was evaluated, and a demand survey (n=169) comparing users’ and non-users’ perceptions along with a librarian survey (n=7) were conducted. Findings reveal that both users (66.3%) and non-users (62.5%) prioritize user demand and community needs analysis, with no statistically significant differences between groups ( =2.15, p=0.91). While the 1st plan achieved results in remodeling and infrastructure, program sustainability was constrained by insufficient specialized personnel, governance structures, and financial continuity. Pyeongchang’s thematic specialization tracks (digital, senior, youth, culture & arts, everyday-life, multicultural) align with regional contexts (average 3.5-3.7 points), but sustained success requires integrated mechanisms: specialized librarian systems, cohort-type program architecture, cross-sector network governance, and diversified funding portfolios. Library-specific implementation models and a phased roadmap (2026-2030) are proposed to transform specialization strategies into sustainable structures.